2016
DOI: 10.1016/j.dadm.2016.12.001
|View full text |Cite
|
Sign up to set email alerts
|

Critical review of the Appropriate Use Criteria for amyloid imaging: Effect on diagnosis and patient care

Abstract: IntroductionThe utility of the Appropriate Use Criteria (AUC) for amyloid imaging is not established.MethodsFifty-three cognitively impaired patients with clinical F18-florbetapir imaging were classified as early and late onset, as well as AUC-consistent or AUC-inconsistent. Chi-square statistics and t test were used to compare demographic characteristics and clinical outcomes as appropriate.ResultsEarly-onset patients were more likely to be amyloid positive. Change in diagnosis was more frequent in late-onset… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
39
1
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(45 citation statements)
references
References 25 publications
4
39
1
1
Order By: Relevance
“…Although the impact of amyloid imaging on management plans was high in that study regardless of whether AUC-like or non-AUClike subjects were considered (88% vs. 86%), a change in diagnosis via amyloid imaging was observed significantly more often in AUC-like than in non-AUC-like subjects (62% vs. 45%). In contrast, Apostolova et al (16) found that changes in diagnosis via amyloid imaging occurred less often in (AUC-consistent) earlyonset cases than in late-onset cases, and treatment changes occurred more often in the early-onset group. Nevertheless, the current AUCs seem to provide a reasonable framework for current clinical use of amyloid imaging.…”
Section: Appropriate Use Criteria (Aucs) For Amyloid Imagingmentioning
confidence: 93%
“…Although the impact of amyloid imaging on management plans was high in that study regardless of whether AUC-like or non-AUClike subjects were considered (88% vs. 86%), a change in diagnosis via amyloid imaging was observed significantly more often in AUC-like than in non-AUC-like subjects (62% vs. 45%). In contrast, Apostolova et al (16) found that changes in diagnosis via amyloid imaging occurred less often in (AUC-consistent) earlyonset cases than in late-onset cases, and treatment changes occurred more often in the early-onset group. Nevertheless, the current AUCs seem to provide a reasonable framework for current clinical use of amyloid imaging.…”
Section: Appropriate Use Criteria (Aucs) For Amyloid Imagingmentioning
confidence: 93%
“…Another study also did not find significant differences in change in management between the AUC and the non-AUC groups [14] (Table 1). …”
Section: Resultsmentioning
confidence: 99%
“…One study reported significantly higher rate of diagnostic change in the AUC group compared to the non-AUC group (62 vs. 45%, p = 0.01) [27]. Similarly, another study reported higher rate of diagnostic change in the AUC group compared to the non-AUC group (53 vs. 23%), but this difference was not statistically significant [14]. In cases where the amyloid-PET scans were positive, the rate of change in diagnosis ranged from 11 to 52% [7, 19, 22, 26].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations